Agribusiness and innovation in the society of liquid modernity. (Revista "Boletín el Conuco", 2021)
The small farmer are immersed in the current and complex dynamics of a consumer society, which is characterized by opportunism and aggressiveness, typical of savage capitalism; vision that I must clarify, at least it is evident in the western world. In this scenario, farm workers as productive actors are subject to dynamics that force them to adopt changes in order to remain in the market. However, the situation of agribusiness in a consumer society, especially that of those small and medium farmers, is characterized by their low economic capacity, therefore access to technological innovation is limited, thus causing a gap social, among those who can or not, access to innovation.